Successful Public Policy in the Nordic Countries - de la Porte, Caroline; Eydal, Guðný Björk; Kauko, Jaakko; Nohrstedt, Daniel; 't Hart, Paul; Tranøy, Bent Sofus (Oxford University Press, 2023)
This book presents 23 in-depth case studies of successful public policies and programmes in Sweden, Denmark, Finland, Norway and Iceland. Each chapter tells the story of the policy’s origins, aims, design, decision-making and implementation processes, and assesses in which respects—programmatically, process-wise, politically and over time—and to what extent it can be considered a policy success. It also points towards the driving forces of success, and the challenges that have had to be overcome to achieve it. Combined, the chapters provide a resource for policy evaluation researchers, educators and students of public policy and public administration, both within and beyond the Nordic region.